In Vitro Antidiabetic Potential and Influence of Neem Oil Extract on Biochemical Indices of Toxicity Following Sub-Acute Administration in Rats (Nigerian Journal of Physiological Sciences, 2025)
Introduction: Neem (Azadirachta indica A. Juss, Meliaceae) is a popular medicinal plant widely sought for its antipyretic, antimalarial, anti-inflammatory, antidiabetic, and antibacterial properties, among others.Methods: Cold-pressed oil from neem seed (NOil) and its cyclohexane-methanol extract (NOHM) were evaluated for their effects on α-amylase and α-glucosidase activities in vitro. Also, NOil (75, 150, and 200 mg/kg) and NOHM (200, 400, and 800 mg/kg) were orally administered to normal experimental rats for 30 days, following which the lipid profile, antioxidant status, and serum and tissue indices of hepatic, renal, and cardiac damage were evaluated.Results: NOHM caused significantly higher (p150 µg/mL). NOHM produced a stronger hypoglycemic effect than NOil. However, no biochemical alteration of toxicological importance was caused by either following subacute administration to animals as the organ-body weight ratio and serum and tissue indicators of organ damage were not adversely altered.Conclusion: The present findings support the safety of NOil and NOHM at the evaluated dosages. The effect of both oil and extract on key carbohydrate-metabolizing enzymes could partly explain the biochemical rationale underlying the popular ethnomedicinal application of the seed in diabetic management.Keywords: Neem oil; toxicity; cyclohexane-methanol extract; α-amylase; α-glucosidase; in vitro